Investigation of the atmosphere with a scanning solar spectropolarimeter - Martinov, Anton O.; Katkouski, Leanid V.; Stanchick, Valery V.; Beliaev, Boris I. (Journal of the Belarusian State University. Physics, 2019)
The article presents the scanning solar spectropolarimeter developed and created in the Institute of Applied Physical Problems of BSU. Software and hardware solutions used in hardware and software development are described. A technique for measuring solar radiation scattered in the atmosphere and a method for reconstructing atmospheric parameters from measurements are presented. Based on the results of the measurements, the polarization characteristics of the scattered solar radiation and the parameters of the atmosphere are calculated.